Translocation of 99mTc labelled bacteria after intestinal ischemia and reperfusion - João, Samir Assi (2004)
Ischemia and reperfusion of the small intestine disrupts gut barrier, causes bacterial translocation and activates inflammatory responses. An experimental study was planned to evaluate if 99mTc labelled Escherichia coli translocates to mesenteric lymph nodes, liver, spleen, lung and serum of rats submitted to mesenteric ischemia/reperfusion. Additionally, it was observed if the time of reperfusion influences the level of translocation. METHODS: Forty male Wistar rats underwent 45 minutes of gut ischemia by occlusion of the superior mesenteric artery. The translocation of labelled bacteria to different organs and portal serum was determined in rats reperfused for 30 minutes, 24 hours, sham(S) and controls(C), using radioactivity count and colony forming units/g (CFU). RESULTS: All the organs from rats observed for 24 hours after reperfusion had higher levels of radioactivity and positive cultures (CFU) than did the organs of rats reperfused for 30 minutes, C and S, except in the spleen (p<0,01). CONCLUSION: The results of this study indicated that intestinal ischemia/reperfusion led to bacterial translocation, mostly after 24 hours of reperfusion